الدافعية للتعلم وعلاقتها بتقدير الذات لدى طلبة الجامعة - عون، سعاد, لمنور، نجوى (جامعة الوادي university of Eloued, 2020)
ملخص: تهدف الدراسة الحالية إلى قياس العلاقة بين الدافعية للتعلم وتقدير الذات لدى طلبة جامعة الوادي، إضافة إلى قياس الفروق في مستوى تقدير الذات لدى طلبة الجامعة ذوي مستوى دافعية للتعلم المرتفعة تبعاً لمتغيرات: الجنس، التخصص الدراسي، المستوى التعليمي. وقد طرحت الدراسة الفرضيات التالية: - توجد علاقة ذات دلالة إحصائية بين مستوى الدافعية للتعلم وتقدير الذات لدى طلبة جامعة الوادي. - توجد فروق ذات دلالة إحصائية في مستوى تقدير الذات لدى طلبة الجامعة ذوي مستوى دافعية للتعلم مرتفع باختلاف جنسهم. - توجد فروق ذات دلالة إحصائية في مستوى تقدير الذات لدى طلبة الجامعة ذوي مستوى دافعية للتعلم مرتفع باختلاف تخصصهم الدراسي. - توجد فروق ذات دلالة إحصائية في مستوى تقدير الذات لدى طلبة الجامعة ذوي مستوى دافعية للتعلم مرتفع باختلاف مستواهم التعليمي. وقد اعتمدت الدراسة على المنهج الوصفي الارتباطي، واختيرت العينة بالطريقة العشوائية الطبقية ذات التوزيع المتساوي من كلية العلوم الاجتماعية، وكلية العلوم والتكنولوجيا بجامعة الوادي للسنة الجامعية: 2019/ 2020، وقد اعتمدت الدراسة أداتين في جمع البيانات هما: مقياس الدافعية للتعلم ومقياس تقدير الذات. وكانت الأساليب الإحصائية المستخدمة مقتصرة على معامل ارتباط "بيرسون" لقياس الفرضية العامة، واختبار"ت" لدلالة الفروق بين متوسطي عينتين مستقلتين ومتساويتين لقياس الفرضيات الجزئية، إذ تم التوصل إلى إثبات الفرضية العامة ونفي الفرضيات الجزئية، وقد تم تفسير نتائج هذه الدراسة في ضوء بعض الدراسات السابقة، وبناءً على أرضية نظرية مسبقة، وختمت الدراسة ببعض الاقتراحات التي من شأنها أن تفتح آفاقاً لأبحاث علمية جديدة. Abstract: The current study aims to know the relationship between motivation to learn and self-esteem among university students, in addition to measuring the differences in the level of motivation to learn among university students with a high level of self-esteem according to variables: gender, academicspecialization, educational level: The study made the following hypotheses : _There is a statistically significant relationship between the level motivation to learn and self-esteem among university students _ There are statistically significant differences in the level of self-esteem of university students with a level of motivation for high learning according To their gender. _There are statistically significant differences in the level of self-esteem among university students with a level of motivation for high learning according to their specialization. _There are statistically significant differences in the level of self-esteem of university students with a level of motivation for high learning according to their different level of education. -The study relied on the relational descriptive approach, and the sample was chosen by the random random medical method of equal distribution from the College of Social Sciences and the College of Science and Technology at the University of the Valley for the academic year: 2019/2020, and the study used two tools in data collection: the motivation measure for learning and the measure of self-esteem. The statistical methods used were limited to the Pearson correlation coefficient for measuring the general hypothesis, and the “T” test for the significance of the differences between the averages of two independent and equal samples to measure the partial hypotheses. Previous studies, based on prior theoretical ground, and the study concluded with some suggestions that would open the horizons for new scientific research.
دراسة ميدانية على عينة من طلبة جامعة الوادي
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: الدافعية للتعلم، تقدير الذات; Motivation à apprendre, estime de soi; Motivation to learn, self-esteem